Distribution of Skill and Encouraging Motivation to Enhance Resilience: Evidence from Accounting Personnel During COVID-19 Crisis - Mohd Danial Afiq bin Khamar Tazilah, Mohamad Rohieszan bin Ramdan, Dayang Rafidah binti Syariff M. Fuad (Tanjung Malim, 2024)
Distribution of Skill and Encouraging Motivation to Enhance Resilience: Evidence from Accounting Personnel During COVID-19 Crisis by Mohd Danial Afiq bin Khamar Tazilah, Mohamad Rohieszan bin Ramdan, Dayang Rafidah binti Syariff M. Fuad